2017
DOI: 10.22146/ipas.10706
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Growth Parameters with Yield of Two Cassava Varieties

Abstract: The correlation of major growth parameters with the yield of cassava in different growth phases was investigated in 2013 and 2014. This experiment was conducted to assess the effect of two cassava varieties and the different growth phases to the yield and yield components. In experiment, the varieties as treatment were arranged in a randomized complete block design (RCBD) with three replications. Two varieties consisted of superior Adira-4 and local varieties Singgah were used. The growth parameters (plant hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Accordingly, in this study, higher values in tuber number, length, and diameter gave higher tuber yield per hectare in variety "Hawassa-4," suggesting that increment of those yield components tends to increase yield per hectare. According to the result of Amarullah et al [40], the growth and yield parameter of cassava have some profound effect on the final tuber yield. In other ways, tuber yield was negatively correlated plant height, signifying that the tuber yield decreases when plant height gets higher (Table 4).…”
Section: Relationship Of Yield and Yield Componentsmentioning
confidence: 99%
“…Accordingly, in this study, higher values in tuber number, length, and diameter gave higher tuber yield per hectare in variety "Hawassa-4," suggesting that increment of those yield components tends to increase yield per hectare. According to the result of Amarullah et al [40], the growth and yield parameter of cassava have some profound effect on the final tuber yield. In other ways, tuber yield was negatively correlated plant height, signifying that the tuber yield decreases when plant height gets higher (Table 4).…”
Section: Relationship Of Yield and Yield Componentsmentioning
confidence: 99%
“…One that affects plant growth and production is seeds with the best quality because it will affect the roots of cassava plants (Legese et al, 2011;Amarullah et al, 2016). Figure 7 shows root growth in seedlings cut using a petokong machine, saw and machete.…”
Section: Seed Growth Testmentioning
confidence: 99%
“…Meanwhile, at 4-8 WAT and 8-12 WAT, SLA had a significant positive correlation with production 0.347 and 0.747, respectively). A study by Amarullah et al [60] concluded that the initial vegetative growth phase was associated with a high assimilation rate for root formation, while the optimum vegetative growth phase significantly affected final yield.…”
Section: Productionmentioning
confidence: 99%
“…e surplus carbon is used for leaf thickening and leaf area growth and for promoting further plant growth depending on the plant's developmental phase. Previous research has shown that plant development influences optimal production in the early growth phase and the maximum vegetative phase and depends on the variety used [60].…”
Section: Productionmentioning
confidence: 99%